Regional and local economic development strategies in the Eastern Cape and guidelines for future development - Nel, E L (Rhodes University, Faculty of Science, Department of Geography, 1997)
Local Economic Development (LED) is an applied economic development strategy which seeks to address site-specific needs through locally appropriate solutions. In this thesis, the faith being accorded to the potential of LED in South Africa is critically examined. The study is based on a detailed examination of the experience of regional development and several emerging cases of LED in the Eastern Cape Province of South Africa. High levels of poverty and unemployment necessitate and justify innovative approaches to address such problems. The thesis examines the potential of LED strategies and identifies applied policy guidelines which can help address the Province's development needs. The theoretical framework of this research is based on a critical examination of international and South African literature dealing with development issues, LED and localities theory. A detailed documentary examination of early LED endeavours and the experience of regional development in the present century was undertaken. Results suggest that LED is not a new concept and that regional development, through its political bias, achieved only limited success. Contemporary examples of LED were identified and examined through detailed site-specific investigations. This was carried out through the use of semistructured interviews supplemented by participatory rural appraisal and questionnaire surveys which served as a means to triangulate the results. The research findings indicate that regional development, as applied in the study area, did not lead to the establishment of a permanent industrial base. In terms of the concept of LED, it is apparent that it has allowed for socio-political empowerment but has only improved economic conditions in the more well-endowed case-studies. In these areas, positive antecedent conditions and the key role played by community supportive nongovernmental organizations is apparent. Despite the limited degree of success which many initiatives attain, the thesis regards LED as a development alternative for areas which are unlikely to draw in external investment. Some of the key contributions of the thesis include the advancement of a refined typology of LED, the development of a research schedule to investigate and assess LED initiatives and the postulation of appropriate development guidelines and theoretical constructs.
Keywords: Community development -- South Africa -- Eastern Cape -- Case studies; Community development; Community development -- South Africa -- Eastern Cape; Eastern Cape (South Africa) -- Economic conditions